Second and Third Trimester Fetal Death in the Setting of COVID-19: A California 2020 Case Series. Issue 2 (23rd April 2022) - Plotzker, Rosalyn E.; Sowunmi, Similoluwa; Eckert, Valorie; Barnes, Emily; Ngo, Van; Stockman, Lauren J.; LeMarchand, Chloe; Halai, Umme-Aiman
Abstract : Abstract: Maternal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the second and third trimesters of pregnancy may impact fetal development via vertical transmission, complications of coronavirus disease 2019 (COVID-19), or placental injury. However, potential associations between prenatal SARS-CoV-2 infection and fetal loss are not well understood. This case series of thirteen second and third trimester fetal losses reported by local public health departments to California's state public health surveillance included maternal clinical and demographic characteristics as well as placental pathology, fetal autopsy reports, and coroner report. There was no evidence that maternal COVID-19 disease severity, placental injury, or SARS-CoV-2 vertical transmission contributed to pregnancy loss. However, this case series is a limited sample; more research is needed to identify factors of prenatal SARS-CoV-2 that may contribute to fetal death in the second and third trimesters.